PEMBELAJARAN LUAS DAERAH BANGUN DATAR DI SEKOLAH DASAR - Yuza, Arlina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
One characteristic of good mathematics learning is the presentation of learning based onthe theory of learning psychology. This means that the teacher must design a lesson thatsuits the stages of a student's mental development. The stage of mental development ofelementary school students is at the concrete operational stage because their age is in therange of age 7 to 11 years. Therefore, mathematics learning in elementary school shouldbe able to facilitate students to acquire concepts. Learning to wake up flat becomes a veryimportant thing to note because this material becomes a prerequisite on the matter ofwaking up space. The concept of two-dimentional figureshould be taught in a guidedmanner to the students, not just memorizing the formula alone.Key Words: two-dimentional figure, mathematics, elementaray school